Spatial inequality of housing value changes since the financial crisis. (February 2020) - Li, Han; Wei, Yehua Dennis
Abstract: The financial crisis has dramatically reshaped the map of inequality; in particular, wealth has been redistributed because of fluctuations in the prices of equities and housing. However, since the explanation of this issue has by default been seen as economists' responsibility, the spatial dimension of the financial crisis still remains unexplored, especially at the intra-urban level. This study examines the local geographies of the housing value bust (2008–2012) and boom (2012–2016) since the financial crisis, with an explicit emphasis on their impacts on urban inequality in Salt Lake County, Utah. We find that housing value changes differ across space and appear strongly associated with the spatial distribution of neighborhood conditions and urban amenities. Additional regressions confirm that a city's housing market volatility is amplified by uneven distribution of physical and service amenities and residential segregation. Moreover, the significance level of local attributes changes over the bust-boom cycle of the housing market. The comparison between bust and boom models suggests that the value of houses enjoying shade from trees and proximity to jobs, places of worship, and good public schools are more resilient, experiencing less value drop in an economic bust, but also less increase in a boom. Other amenities such as public transport, hospitals, parks, and restaurants could be interpreted as types of discretionary consumption, which positively contribute to housing value volatility. Neighborhood conditions, especially white-Hispanic segregation, significantly contribute to housing value fluctuation. Hispanic communities in Salt Lake County tend to experience more loss of property value in a bust and gain more in a boom. Thus, our study suggests that a more balanced urban distribution of employment, races, and amenities would significantly enhance local economic stability by smoothing fluctuations of business cycles at the local level. Highlights: Housing market volatility is amplified by uneven distribution of physical and service amenities and residential segregation. Value of housing enjoying green space and proximity to jobs and good public schools are more resilient. Amenities of discretionary consumption positively contribute to housing value volatility. Neighborhood segregation also significantly contributes to housing value fluctuation. A more balanced urban distribution of employment, races, and amenities would significantly enhance local economic stability.